Morphology And Performance Evaluation Of Polyethersulfone/Zinc Oxide (PES/ZnO) Mixed Matrix Membrane Fabricated Using Non Solvent Additive - Sugumaran, Jayasree (Universiti Sains Malaysia, 2018)
The effect of nanoparticles (NPs) in the non solvent additive modified membrane is studied in this paper. The ratio of acetone/NMP is manipulated and its effect to morphology and performance of membrane is observed and the best performing ratio of acetone/NMP is used to fabricate a mixed matrix membrane with ZnO-NPs. Addition of acetone results in thick skin layer followed by reduced finger like macrovoids which improved the rejection but decreased pure water flux. Acetone incorporation into membrane reduces hydrophilicity while, the surface roughness decrease slightly. The tight skin layer with reduced porosity and pore size of acetone modified membrane can minimize the fouling effect. The FRR value of acetone/NMP ratio of 0.05 is as high as 97.93 % but the value decreased by 24.92% when the ratio of solvent is 0.20. High concentration of acetone reduce the hydrophilicity cause several fouling. The incorporation ZnO-NPs into the NSA modified membrane can improve the hydrophilicity and porosity, hence the pure water flux improves. But, the irreversible fouling of membrane with 0.5 wt.% of ZnO increase significantly compared to the membrane with acetone alone which is again due the open pore in ZnO modified membrane. But, the Flux Reduction Ratio (FRR) values improves with the increase of ZnO, as the membrane become hydrophilic reduce the humic acid adsorption. The pore blocking behaviour PES/NMP/Acetone and PES/NMP/Acetone/ZnO are evaluated based on 4 pore blocking models. The cake filtration is the dominant pore blocking cause for both membrane at initial (20 min) and final stage (21 min to 60 min). But, the coefficient of determination, R2 value for other pore blocking models is nearly same as the cake filtration so, fouling may be due the combination of all the models.